CHANGING PATTERNS OF CHILD REARING PRACTICE IN BADAGRY AREA OF LAGOS STATE: IMPLICATION FOR DELINQUENT BEHAVIOUR - Emmanuel, Ajiboye Olanrewaju; Akinyemi, Atere Adewole; Nimotalai, Olufunmi Afolshade (European Scientific Journal, ESJ, 2012)
Child rearing practices is a form of socialization process whereby a new member is trained and nurtured in such a way that he/she learns the ways of life of his people in order to become a useful member of the society and this provides opportunity for the survival of the society. However, faulty socialization or child rearing practice has resulted in to delinquent behavior among the young members of the various families in Nigeria today with its attendant social concomitant effect on the larger society. This study is an exploratory one. It therefore focuses on Changing patterns of child rearing practice in Badagry area of Lagos State, Nigeria: Implication for delinquent behaviour. Triangulation method was used for data collection. A multi-stage sampling procedure was adopted to select 100 respondents. Chi-square technique was used to test the hypothesis for the study.The study found positive relationship between pattern of child rearing practices and personality and delinquent behavior formation among the people of Badagry. The study also found positive association between effective socialization by parents and child’s positive attitudes towards life. It was recommended that Parents should put more effort to ensure that their children are adequately provided for and morally groomed. This call to question the issue and justification for family planning which among other objectives seeks to ensure that parents only give birth to children they can comfortably cater for. Government should therefore assist through education and enlightenment campaign that could help in the reduction of delinquent behavior among the youth in Nigeria at large.